Idealisasi TVRI sebagai TV Publik: Studi “Critical Political Economy" - Lisa Adhrianti (MediaTor)
In the beginning, media was established as an integral part of public sphere. As the world changed, media turned to be commercialized as commodity by mass distribution operation. Media was also sold to advertisers which use media facilities to reach their customers. This turnover had moved media more and more far away from the ideal of public sphere. It amounted when contents of media were dominated by less educated and less morality program. In order to implement public broadcasting media, an effort to create public sphere was badly needed. One of such effort was  transformation of TVRI status to Public   Broadcasting Organization by UU No. 32/Th. 2002. But, in reality, the operationalization of TVRI as Public TV still face some obstacles. This paper examines several regulation barriers faced by TVRI that prevent an ideal public sphere.